PELATIHAN BAGI SISWA MTS AL MUDDATSIRIYAH DALAM MENGGUNAKAN MULTIMEDIA INTERAKTIF SEBAGAI ALAT BANTU MEMAHAMI KONSEP FISIKA DI MASA PANDEMI - Hermansyah; Syafruddin; Tursina Ratu; Nurhairunnisah; Musahrain (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic continues to this day, this causes the learning process in the Education Unit to be carried out online/in the network or better known as BDR (Learning from Home). This kind of learning process really demands independent learning from students. To make it easier for students to learn, the purpose of this training is to train students in using interactive multimedia as a tool to understand physics concepts. This activity was carried out at MTs Al-Muddatsiriyah Central Jakarta with full Online implementation via Zoom. The implementation method used consists of three stages, namely the preparation, implementation, and evaluation stages. The results obtained from this activity are positive responses in the form of enthusiastic students and teachers during the activity and students are easier to understand physics concepts by using interactive multimedia.